2016
DOI: 10.1016/j.clae.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cyst wall is an effective strategy in improving the efficacy of marketed contact lens disinfecting solutions against Acanthamoeba castellanii cysts

Abstract: A B S T R A C TAcanthamoeba cysts are highly resistant to contact lens disinfecting solutions. Acanthamoeba cyst wall is partially made of 1,4 b-glucan (i.e., cellulose) and other complex polysaccharides making it a hardy shell that protects the resident amoeba. Here, we hypothesize that targeting the cyst wall structure in addition to antiamoebic compound would improve the efficacy of marketed contact lens disinfecting solutions. Using chlorhexidine as an antiamoebic compound and cellulase enzyme to disrupt c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…This is likely due to the ability of cellulase to destroy cyst walls by degrading cellulose, allowing chlorhexidine to target the resident trophozoite within and ultimately leading to its death. This is consistent with our previous findings which showed that the addition of cellulase enzyme together with chlorhexidine enhanced the efficacy of contact lens solutions marketed in Pakistan (Abjani et al, 2016). As cellulose synthesis is limited to plants, yeast, and some bacteria, it is likely to have minimal side effects against human cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is likely due to the ability of cellulase to destroy cyst walls by degrading cellulose, allowing chlorhexidine to target the resident trophozoite within and ultimately leading to its death. This is consistent with our previous findings which showed that the addition of cellulase enzyme together with chlorhexidine enhanced the efficacy of contact lens solutions marketed in Pakistan (Abjani et al, 2016). As cellulose synthesis is limited to plants, yeast, and some bacteria, it is likely to have minimal side effects against human cells.…”
Section: Discussionsupporting
confidence: 92%
“…The supernatant was aspirated followed by addition of 200 μL of six different contact lens disinfectants to resuspend bacteria. Following 6 h of incubation, bacteria were enumerated by plating as described previously (Abjani et al, 2016). Bacteria incubated with PBS alone and bacteria incubated with gentamicin 100 μg per mL were used Table 1 List of contact lens disinfectants tested in the present study together with their ingredients, manufacturer, type of solution and Minimum recommended disinfection time (MRDT).…”
Section: Bactericidal Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…It is far more economical to develop effective contact lens disinfectants against Acanthamoeba. Although the ability of amoebae to switch phenotypes into a dormant cyst form is a major hindrance in the development of effective contact lens disinfectants and/or chemotherapeutic approaches, recent studies have shown that the addition of cellulase enzyme to disrupt cyst wall structure renders amoeba cysts susceptible to the effects of antiamoebic drugs (92). The combination of antiamoebic agent and cellulase enzyme was shown to abolish the viability of both cysts and trophozoites.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Once cyst walls are degraded, it is easier to target Acanthamoeba . This concept was proven by our team [ 13 ] who showed that targeting Acanthamoeba cysts with cellulase enzyme in combination with chlorhexidine can effectively abolish Acanthamoeba cyst viability. In contrast, cellulase or chlorhexidine alone had limited effects against Acanthamoeba cysts [ 13 ].…”
Section: Targeting the Cyst Wallmentioning
confidence: 98%